Regional Language Teachers Perception Of Makassar Languange Book. - Ridha Reskiyanti; Hajrah Hajrah (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
Regional Language Teachers Perception Of Makassar Languange Book.The purpose of this study was to describe the teacher's perception of the Makassar language textbook. The data in this study is the local language teacher's perception of the seventh grade Makassar language textbook. The sources in this study were Regional Language Teachers, totaling 3 people. The data collection in this study was a questionnaire technique and an interview technique. This study was processed by using the percentage test (%), then described and reinforced by the results of interviews, the data obtained were analyzed using the percentage formula. The results of research and data analysis that have been carried out regarding the perception of Regional Language teachers towards Makassar language textbooks for class VII that Makassar language textbooks for class VII publishers UD MANDIRI/CV MITRA SAHABAT with a percentage of 83.35% in the Very Easy category and strengthened by the results of interviews.